An Examination of the Mergers and Acquisitions Involving PT Goto Gojek Tokopedia Tbk - Dana Syahputra Barus; Elida Elfi Barus (Majapahit Journal of Islamic Finance and Management, 2023)
The merger of Gojek and Tokopedia, two leading start-ups in Indonesia, culminated in the creation of a unified entity known as GoTo on May 17th, 2021. This strategic integration marks a significant milestone, positioning GoTo as a major player in the Southeast Asian market. The primary objective of this study is to comprehensively analyze the factors and challenges inherent in the GoTo E-Commerce Merger process. Employing a qualitative research methodology, this study delves into the complexities of the merger, shedding light on critical aspects. The merger not only facilitates geographical expansion for GoTo but also positions it strategically to enhance operational effectiveness and efficiency. This geographical expansion is a crucial aspect, as it allows GoTo to tap into other Southeast Asian markets, creating a formidable presence that enables it to compete more effectively with prominent technology conglomerates. However, the post-merger scenario for PT GoTo has not been without its share of challenges. The study identifies and scrutinizes four major challenges faced by the company in the aftermath of the merger. This study provides a nuanced examination of the GoTo E-Commerce Merger, offering valuable insights into the underlying factors and challenges faced by PT GoTo. Through a qualitative research methodology, the study contributes to a comprehensive understanding of the dynamics at play in the post-merger landscape, shedding light on critical aspects that demand strategic attention and management.